Estimating the prevalence of key healthcare-associated and opportunistic infections in Australian transplant and cancer populations: protocol for the PROSPER point prevalence study - Lisa Hall; Leon J Worth; Monica A Slavin; Priya Garg; Nikhil Singh; Alice J Liu; Michelle K Yong (BMJ Open, 2025)
Introduction The immunocompromised host (ICH) is at increased risk for a range of opportunistic and healthcare-associated infections (OI/HAIs). With increased use of novel therapeutics and prolonged survival, the malignancy and transplant population is a particularly vulnerable and expanding subgroup. In the absence of a coordinated Australian infection surveillance programme, estimates of the prevalence of OI/HAIs for the high-risk ICH population are yet to be established. Approaches to infection prevention and control (IPC) are also non-standardised across healthcare facilities (HCFs). This study aims to provide data on key pathogen prevalence and comparative IPC and infection monitoring practice amongst the Australian cancer/transplant population to inform future consensus ICH-specific policy.Methods and analysis The first multi-site adapted point prevalence survey (PPS) for OI/HAIs in the high-risk ICH population will be conducted across several Australian public HCFs providing inpatient (IP) care for adult transplant (solid organ/haematopoietic stem-cell)±malignancy (haematological/oncological) patients. Surveillance methodology using the European Centre for Disease Prevention and Control (ECDC) PPS protocol modified for the ICH will be applied. ICH-adapted ECDC and Centres for Disease Control and Prevention (CDC)/National Healthcare Safety Network (NHSN) surveillance case definitions will be used for key HAIs and diagnostic criteria for select OIs. Potentially eligible cancer and transplant patients will be identified for sampling by active antimicrobial use. Infection data, patient-level risks and correlates for HCF impact will be collected from medical records. To contextualise infectious rates, IPC and surveillance strategy will be explored through qualitative interviews with IPC personnel at each sampling site. The prevalence of infection will be approximated from the proportion with infection in the sample screened, and descriptive data analysis will be used to support the expected outcomes of this study, which includes providing a unique insight into infectious disease trends alongside current IPC and surveillance processes within this highly specialised population.Ethics and dissemination Ethical approval has been obtained from the Peter MacCallum Cancer Centre (PMCC) Human Research Ethics Committee (HREC/112164/PMCC) via the National Mutual Acceptance Scheme. Research findings will be disseminated through peer-review publication and conference presentation and contribute to future work on consensus IPC and surveillance guidelines.